اثر الاسئلة السابرة في تحصيل طلاب الصف الرابع العام لمادة التاريخ (Journal Of Educational and Psychological Researches, 2010)
The importance of teaching methods and procedures comes from the nature and significance of the questions raised inside the classroom. That is, because questions, in fact, are the means of communication and interaction in the class situation. Therefore they are considered as indispensible elements in any teaching approach. Furthermore, it is noticeable that the majority of teachers fail in using them, for questions are often casted spontaneously and without pre-planning. Hence, a delay may occur in realizing the pre-set objectives, and let alone the dominance of stereotyped questions, especially when the teachers focus on a type of question which can be directly answered from the text-book.                 However, the set of questions, included in the text-book, seems not to provide the learners with any encouragement, i.e., they do not help the student to probe into thinking, and consequently not lead to thoughts association, which makes them fail to make any conclusions out of the material of the lesson. Aims of the Study                Impact of the probing questions on the preparatory school fourth year general students’ achievements in the History Lesson.Hypothesis of the Study               No statistically-significant difference could be found at the level 0.05 between the achievements’ marks average between students taught under the probing questions procedure and those taught under the traditional procedure without carrying out any further activities.Limits of the studyA sample was taken from the preparatory school fourth year general students/ Morning classes/ in Baghdad Governorate/ Alrussafah 2th / the academic year 2008 - 2009  Basic Terms Used in the Study• Probing Questions• Achievement• HistoryChapter Two surveys the previous study on the probing questions and their impact on the students’ achievementsChapter Three demonstrates the study methodology as follows:Firstly: Experiment designing – the study adopted an experiment design consists of an experimental group and a control group plus a post-achievement test.Secondly: the study community- morning classes preparatory school students in Baghdad Governorate/ Alrussafah 2th / the academic year 2008 – 2009Thirdly: Study sample – the number of the two sections students, representing both,  the experimental group and the control group , was (36) students for the experimental group and (36) students for the control group• For equivalency, the study used the variables elements  ( chronological age/months, parents qualifications,  final test History Lesson’s marks of third year/intermediate , pre-test marks of History Lesson)• Depending on the general objectives and the History material contents to be taught in the course of the experiment , the study designed 13 behavioral objectives , distributed according to Bloom’s classification, among the three levels of the cognition field ( cognition, understanding and application).• An achievement test was designed for the two research groups, in which a number of statistical means were used : ( T-test,   equation of difficulty and item distinction ; Person’s correlation coefficient and Spearman-Brown equationChapter Four demonstrates the findings and their justificationFurthermore, in this chapter, the study demonstrates the findings reached by the study in compliance with the Study aim and hypothesis (the study hypothesis was refuted, because the findings has shown that a statistically significant difference could be found between the marks of the experimental group and the control group in favor of the experimental group       Fourthly: Conclusions- in the light of the reached findings, it could be concluded that:1 – Probing questions can would encourage the students to innovate, doing more training and scientific research in compliance with their experience level and maturity.2 – Within the limits of this study conducting, the probing questions have proved efficiency in increasing the students’ achievements, and they have great positive effect on how to study History Lesson’s material meaningfully.Fourthly: Recommendations- in the light of the reached findings, it could be recommended:• History Lesson’s teachers should be aware of the Probing questions, and the way they are utilized by using the text-books• Instructing the teachers of the social sciences to follow the Probing questions procedure when teaching the history Lesson materialsFifthly: Suggestions- it is suggested that it will be useful to carry out similar studies to this on the students of the preparatory fifth and sixth year students